STRATEGI GURU TADIKA MALAYSIA DALAM MEMBENTUK KEBIASAAN IBADAH ANAK - Nazura Purba, Nazwana; Zuliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the strategies implemented by teachers at Tadika Al-Fikh Orchard Malaysia in developing children's worship habits at an early age. Early childhood is a critical period for character formation, including the internalization of religious values. However, in practice, teachers face various challenges such as children's short attention span, differences in family backgrounds, and limited time in learning activities. This research employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation involving teachers and students at Tadika Al-Fikh Orchard. The data were analyzed using qualitative data analysis techniques, including data reduction, data display, and conclusion drawing. The results show that teachers apply several strategies, namely role modeling, habituation of worship practices, and motivational reinforcement. Role modeling by teachers becomes the most influential factor, as children tend to imitate behaviors observed in their environment. In addition, consistent habituation and a supportive religious environment contribute significantly to the development of children's worship habits. Collaboration between teachers and parents also plays an important role in ensuring continuity between school and home environments. Despite several challenges, such as differences in children's characteristics and family backgrounds, the implementation of appropriate and engaging strategies can effectively foster children's religious habits. This study contributes to the development of early childhood religious education by emphasizing the importance of integrated and consistent strategies in shaping children's spiritual character.